A SIS membrane based on hydroxyapatite coating, preparation method and application thereof

By preparing a hydroxyapatite coating on the SIS membrane to form a SIS-HA composite membrane, the problem of insufficient periodontal tissue regeneration in existing periodontal disease treatment methods is solved, and better osteoinductive activity and immune regulation are achieved. Effect.

CN115737939BActive Publication Date: 2025-01-21SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211483525.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-01-21
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The existing treatment methods for periodontal disease have not yet achieved complete regeneration of periodontal tissue, and the existing membrane materials have shortcomings in osteoinductive activity, space maintenance ability and immune response.

Method used

A SIS membrane based on hydroxyapatite coating was used to prepare a SIS-HA composite membrane through mineralization treatment to enhance its osteoinductive activity and immunomodulatory ability.

Benefits of technology

It achieves periodontal tissue regeneration, improves osteoinductive activity and immune regulation capabilities, and ensures the safety and ease of operation of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115737939B_ABST
    Figure CN115737939B_ABST
Patent Text Reader

Abstract

The present invention discloses a SIS membrane based on hydroxyapatite coating, a preparation method and application thereof, and belongs to the technical field of biomedical materials. The preparation method comprises: selecting a small intestine jejunum segment to prepare a SIS membrane; after the SIS membrane seals the mucosal layer, it is placed in a mineralizing solution and soaked for 1.5 to 3 hours, and after mineralization, washing and freeze-drying are performed to obtain a SIS-HA composite membrane with hydroxyapatite mineralization; and the application of the SIS membrane based on hydroxyapatite coating prepared by the method of the present invention in the preparation of materials for treating periodontal disease. The present invention adopts a pig small intestine jejunum segment to prepare a SIS membrane, and innovatively prepares a SIS-HA membrane with a HA coating by a biomineralization method. The experiment verifies that the membrane has good biocompatibility, is conducive to cell adhesion, proliferation and migration, and has the dual characteristics of immunoregulation and osteogenic induction. Animal experiments have obtained satisfactory periodontal tissue regeneration effects, and the new SIS-HA composite membrane with a HA coating provided by the present invention has broad application prospects in periodontal tissue regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a SIS membrane based on hydroxyapatite coating, a preparation method and application thereof. Background Art

[0002] Periodontal disease is a chronic infectious disease caused by plaque microorganisms, which usually leads to inflammation of periodontal tissues, progressive attachment loss, alveolar bone resorption, and ultimately tooth loosening and loss. It is the most common cause of tooth loss in adults. The ultimate goal of periodontal disease treatment is to achieve functional repair and regeneration of damaged periodontal supporting tissues (including gums, periodontal ligament, alveolar bone, and cementum). However, the realization of this goal is still a difficulty and research focus in periodontal disease treatment today. At present, the core of clinical periodontal treatment is to remove tartar and plaque, remove the initiating factors of the disease, and stop the progression of the disease, but the complete regeneration of lost periodontal tissues has not yet been achieved. Guided Tissue Regeneration (GTR) is the main treatment method currently used in clinical practice for periodontal tissue regeneration. This technology uses membrane materials as a barrier to block the growth of gingival epithelium along the root surface during the healing process, block the contact between gingival connective tissue and the root surface, and provide a certain space to guide periodontal ligament cells with the ability to form new attachments to preferentially occupy the root surface, thereby forming new cementum on the root surface that was originally exposed to the periodontal pocket, and embedding periodontal ligament fibers to form periodontal tissue regeneration. Among them, the barrier membrane is the key to GTR technology. The ideal barrier membrane should create a microenvironment suitable for periodontal tissue regeneration in the periodontal defect area, recruit functional cells related to periodontal regeneration around the defect to migrate to the defect area, and induce functional cells to differentiate into periodontal tissue. It should have the following characteristics: (1) good biological activity; (2) good mechanical barrier to block epithelial cells and fibroblasts outside the defect; (3) good space maintenance to ensure the regeneration space of alveolar bone, periodontal ligament and cementum; (4) good clinical operability; (5) the degradation rate of the absorbable membrane should match the regeneration rate of periodontal tissue. At present, most of the membrane materials used in clinical GTR are commercial collagen membranes, such as Bio-Gide, Haiao, etc., which still have some shortcomings: 1. Insufficient bone induction activity; 2. Insufficient space maintenance ability; 3. Failure to take into account the characteristics of periodontal soft and hard tissue regeneration; 4. Poor clinical operability, etc. At the same time, for clinical gingival defects and deficiencies, periodontal soft tissue augmentation is mainly carried out through local soft tissue flap treatment, autologous connective tissue free flap transplantation and membrane transplantation to close the wound and reconstruct gingival tissue. Among them, autologous connective tissue free flap transplantation, as the "gold standard" for the treatment of gingival defects, usually has problems such as limited soft tissue augmentation range, the need to open a second surgical area, complex surgical process, increased patient discomfort, easy contraction of free flaps, and large color contrast with adjacent gingival tissues that cannot achieve aesthetic effects. However, allogeneic membrane transplantation has certain immunogenicity, is prone to immune rejection, and has a severe inflammatory reaction. In addition, allogeneic dermal matrix membranes have the disadvantages of limited donors, high prices, and ethical factors.Therefore, it is urgent to find a new type of biofilm in clinical work that can promote the increase of periodontal soft and hard tissues without causing immune rejection reaction, is safe and reliable, has sufficient source, low price, and is easy for patients to accept. This is of great significance to promoting the control of oral diseases.

[0003] Porcine small intestinal submucosa (SIS) is a natural acellular matrix material, mainly composed of type I and type III collagen, and also contains a small amount of type IV and type VI collagen, a variety of glycosaminoglycans, growth factors and antimicrobial peptides. SIS has a typical collagen fiber tissue structure, and the collagen fibers are preferably arranged along the natural longitudinal axis of the small intestine. This preferred fiber orientation will produce anisotropic biomechanical behavior. Some scholars have found that the serosal surface of SIS presents a loose fiber mesh structure with pore sizes ranging from submicron to micron, while the mucosal surface structure is denser. These structural differences make the penetration of substances direction-dependent, and the permeability from the serosal side to the mucosal side is more than 4 times that of the opposite direction. Since SIS was first used in vascular repair in 1966, it has gradually become a research hotspot in the field of tissue repair. At present, SIS and its derivative materials have been approved by the US FDA for clinical treatment of soft tissues such as heart, bladder, and vagina. Researchers have achieved complete decellularization of SIS through different preparation methods, showing good biocompatibility, but all current preparation methods will cause the microstructure and bioactive components of SIS to be damaged to varying degrees. A large number of studies have shown that SIS has been successfully used as a xenogeneic scaffold material in many models without producing immune-mediated inflammatory responses, and the infection phenomenon observed after SIS transplantation is less than that of other transplant materials. In summary, SIS is suitable for the preparation of new guided tissue regeneration barrier membranes due to its good biocompatibility, biodegradability, mechanical properties, antibacterial activity and low immunogenicity, but the direct application of SIS membranes in periodontal tissue regeneration still has problems such as relatively low bone induction activity.

[0004] The main inorganic component of human bone is hydroxyapatite (HA), which has good osteoinductive ability and stable performance under physiological environment. It can provide good support for the adhesion and growth of bone cells, and provide nuclei for the calcification of bone cells into bones, play a role in osteoconduction, and is often used to make biological coatings for biomaterials. Studies have reported that collagen membranes doped with HA have better mechanical properties and osteoconductivity. Castilla et al. added HA to SIS solution and prepared a biomimetic SIS-HA sponge through freeze-drying technology. The sponge has high porosity, and the porosity and density of the material will change with the change of HA concentration. This preparation method has good reproducibility and low cost, and is expected to become a potential bone transplant substitute. Sun et al. deposited mineralized SIS (mSIS) on the surface of bone ceramics and successfully constructed a new composite biological scaffold material, which can significantly promote the adhesion and proliferation of rat bone marrow mesenchymal stem cells (BMSCs), and induce osteogenic differentiation of BMSCs through SMAD1 / 5 / 8 and ERK1 / 2 signaling pathways. Implantation into rat skull defects can significantly promote new bone formation. The team replaced bone ceramics with mesoporous bioactive glass (MBG) to prepare mSIS / MBG composite scaffold materials, and the porosity and mechanical properties were significantly improved. Western blot analysis results showed that mSIS / MBG can induce osteogenic differentiation of BMSCs by activating the Wnt / β-catenin signaling pathway, and enhance the angiogenic activity of vascular endothelial cells by activating the PI3K / Akt signaling pathway. The in vivo experimental results also showed better osteogenic and angiogenic activity. Parmaksiz et al. assembled bovine SIS into a multilayer scaffold material using HA particles and polycaprolactone as binders. The results of morphological observation showed that it had a uniform multilayer porous structure and uniform distribution of HA particles; the results of mechanical tests showed that it had good mechanical stability; the results of cell experiments showed that it had a good osteoinductive effect on BMSCs even without the use of any exogenous osteoinductive agent. The molecular mechanism of HA promoting osteogenic differentiation is still unclear. It may be that calcium ions from HA are involved in various physiological activities of cell osteogenic differentiation and the conduction of electrical signals, and biomaterials containing calcium phosphate can induce osteogenic differentiation of stem cells through adenosine signaling. Coating technology is often used for the modification of biomaterials. HA coating mainly includes electrochemical deposition, plasma spraying, chemical precipitation and chemical cross-linking. Among them, electrochemical deposition and plasma spraying often need to be carried out under harsh conditions such as high temperature, which are not suitable for the modification of extracellular matrix biomaterials. Therefore, it is urgent to study a SIS membrane to enhance its osteoinductive activity and use it for the regeneration of periodontal soft and hard tissues. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a SIS membrane based on hydroxyapatite coating, a preparation method and application thereof.

[0006] The object of the present invention is achieved by the following technical solution: a method for preparing a SIS membrane based on a hydroxyapatite coating, which comprises the following steps:

[0007] S1. Preparation of SIS membrane: Select the small intestine jejunum segment to prepare SIS membrane;

[0008] S2. Mineralization treatment: After sealing the mucosal layer of the SIS membrane prepared in step S1, soak it in a mineralizing solution for 1.5 to 3 hours. After mineralization, wash and freeze-dry to obtain a hydroxyapatite-mineralized SIS-HA composite membrane, wherein the mineralizing solution is a mixed solution of sodium chloride, potassium chloride, calcium chloride, magnesium chloride hexahydrate, disodium hydrogen phosphate and sodium bicarbonate.

[0009] Furthermore, in step S1, the SIS membrane is prepared using the jejunum segment of pig small intestine.

[0010] Furthermore, step S1 also includes a pre-treatment step of the small intestine jejunum segment, specifically: the small intestine jejunum segment is cleaned and cut into segments with a length of 8 to 12 cm, cut longitudinally with a blade, and the mucosal layer, muscularis externa and serosa are completely peeled off, and the remaining submucosal layer and mucosal basal layer are used to prepare the SIS membrane.

[0011] The specific operation of preparing the SIS membrane can also be: placing the submucosal layer and the mucosal basal layer in a mixed solution of 0.1% peracetic acid and 4% ethanol and stirring continuously for 1.5 to 2.5 hours at a stirring rate of 250 to 350 rpm, then washing with PBS for 10 to 20 minutes, and then cleaning with deionized water.

[0012] The specific operation of preparing the SIS membrane can be: soaking the submucosal layer and the mucosal basal layer in a mixed solution of methanol and chloroform with a volume ratio of 1:1 for 10 to 15 hours, and rinsing with deionized water; then incubating in EDTA containing trypsin at 37°C for 10 to 15 hours, and rinsing with saline, wherein the mass percentage content of trypsin is 0.05%, and the mass percentage content of EDTA is 0.05%; then continuously stirring in a mixed solution of 0.9% sodium dodecyl sulfate and 0.9% sodium chloride for 3 to 5 hours; finally soaking in a mixed solution of 0.1% peracetic acid and 20% ethanol for 25 to 35 minutes, and rinsing with saline.

[0013] The specific operation of preparing the SIS membrane can also be: first soak the submucosal layer and the mucosal basal layer in 10mM EDTA with pH=12 for 14-18h; then soak in 1M NaCl solution with pH=1 for 6-10h, soak in 1M NaCl PBS solution for 14-18h, soak in 10mM PBS solution with pH=7.4 for 1.5-2.5h, and finally rinse with sterile water.

[0014] Furthermore, the mass percentage concentration of each raw material in the mineralized solution in step S2 is: 3-8% sodium chloride, 0.02-0.05% potassium chloride, 0.1-0.5% calcium chloride, 0.05-0.15% magnesium chloride hexahydrate, 0.08-0.2% disodium hydrogen phosphate, and 0.05-0.15% sodium bicarbonate.

[0015] Furthermore, the mass percentage concentration of each raw material in the mineralized solution in step S2 is: 5.84% sodium chloride, 0.036% potassium chloride, 0.28% calcium chloride, 0.1% magnesium chloride hexahydrate, 0.12% disodium hydrogen phosphate, and 0.084% sodium bicarbonate.

[0016] SIS membrane based on HA coating prepared by the above method.

[0017] The application of HA-coated SIS membrane prepared by the above method in the preparation of materials for treating periodontal disease.

[0018] The present invention has the following beneficial effects:

[0019] (1) The present invention uses the jejunal segment of the small intestine of pigs to prepare the SIS membrane, which has a wide source of raw materials and is highly cost-effective. The SIS-HA composite membrane with HA coating is innovatively prepared by the biomineralization method, wherein only the SIS serosal layer is coated with HA, and the mucosal layer acts as a barrier and is not coated. The coating method is simple and can retain the protein components of SIS itself to the greatest extent.

[0020] (2) The SIS-HA composite membrane prepared by the method of the present invention has excellent physical and chemical properties, is easy to operate in clinical use (good hydrophilicity, easy to adhere to the tissue surface), and is safe in clinical application (has good biosafety, is conducive to cell adhesion, proliferation and migration). It also has excellent dual characteristics of immunoregulation and osteogenic induction, and animal experiments have obtained satisfactory periodontal tissue regeneration effects.

[0021] (3) This application provides three methods for preparing SIS membranes, and experimentally verifies the optimal method for preparing SIS membranes for periodontal tissue regeneration to ensure that they have good decellularization performance and retain the original microstructure of the extracellular matrix. Therefore, the new SIS-HA composite membrane with HA coating provided by the method of the present invention has broad application prospects in periodontal tissue regeneration. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Design a roadmap for the experiment of the present invention.

[0023] Figure 2 This is a comparison of picrosirius red staining of pig duodenum, jejunum and ileum.

[0024] Figure 3 This is a comparison of SEM and cell nuclear staining results of three SIS preparation methods.

[0025] Figure 4 This is a comparison chart of residual DNA detection results of three SIS preparation methods.

[0026] Figure 5 This is a comparison chart of the results of ELISA detection of active factors using three SIS preparation methods.

[0027] Figure 6 This is the SIS EDS diagram.

[0028] Figure 7 This is the EDS diagram of SIS-HA.

[0029] Figure 8 This is a comparison chart of the hydrophilicity of SIS and SIS-HA.

[0030] Fig. 9 Comparison of mechanical properties of SIS and SIS-HA.

[0031] Fig.10 This is a comparison chart of the in vitro degradation rates of SIS and SIS-HA.

[0032] Fig.11 This is a comparison chart of the immune regulation capabilities of SIS and SIS-HA cells.

[0033] Fig.12 This is a comparison of the adhesion ability of SIS and SIS-HA to human periodontal ligament cells.

[0034] Fig.13 This is a comparison of the proliferation ability of SIS and SIS-HA human periodontal ligament cells.

[0035] Fig.14 This is a comparison of the migration ability of SIS and SIS-HA human periodontal ligament cells.

[0036] Fig.15 This is a comparison of the osteogenic differentiation ability of SIS and SIS-HA human periodontal ligament cells.

[0037] Fig.16 This is a comparison of the bone healing effects of SIS and SIS-HA implanted in 3D reconstruction of periodontal bone defects in rats.

[0038] Fig.17 This is a comparison of the histochemical staining results of SIS and SIS-HA implanted in periodontal bone defects in rats. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and embodiments, and the protection scope of the present invention is not limited to the following:

[0040] Example 1: A method for preparing a SIS membrane based on a HA coating, comprising the following steps:

[0041] S1. Preparation of SIS membrane: The SIS membrane was prepared by selecting the small intestine jejunum segment, specifically: the small intestine jejunum segment was cleaned and cut into segments with a length of 8 to 12 cm, and the segments were cut longitudinally with a blade, and the mucosal layer, the muscularis externa and the serosal layer were completely peeled off, and the remaining submucosal layer and mucosal basal layer were placed in a mixed solution of 0.1% peracetic acid and 4% ethanol and stirred continuously for 1.5 hours at a stirring rate of 250 rpm, and then washed with PBS for 10 minutes, and then cleaned with deionized water;

[0042] S2. Mineralization treatment: After sealing the mucosal layer of the SIS membrane prepared in step S1, soak it in a mineralizing solution for 1.5 hours. After mineralization, wash and freeze-dry to obtain a hydroxyapatite-mineralized SIS-HA composite membrane, wherein the mineralizing solution is: 3% sodium chloride, 0.02% potassium chloride, 0.1% calcium chloride, 0.05% magnesium chloride hexahydrate, 0.08% disodium hydrogen phosphate, and 0.05% sodium bicarbonate.

[0043] Example 2: A method for preparing a SIS membrane based on a HA coating, comprising the following steps:

[0044] S1. Preparation of SIS membrane: The jejunal segment of the small intestine was selected to prepare the SIS membrane, specifically: the jejunal segment of the small intestine was cleaned and cut into segments of 8 to 12 cm in length, and the segments were cut longitudinally with a blade, and the mucosal layer, the muscularis externa and the serosal layer were completely peeled off, and the remaining submucosal layer and mucosal basal layer were placed in a mixed solution of 0.1% peracetic acid and 4% ethanol and stirred continuously for 2.5 hours at a stirring rate of 350 rpm, and then washed with PBS for 20 minutes, and then cleaned with deionized water;

[0045] S2. Mineralization treatment: After sealing the mucosal layer of the SIS membrane prepared in step S1, soak it in a mineralizing solution for 3 hours. After mineralization, wash and freeze-dry to obtain a hydroxyapatite-mineralized SIS-HA composite membrane, wherein the mineralizing solution is: 8% sodium chloride, 0.05% potassium chloride, 0.5% calcium chloride, 0.15% magnesium chloride hexahydrate, 0.2% disodium hydrogen phosphate, and 0.15% sodium bicarbonate.

[0046] Example 3: A method for preparing a SIS membrane based on a HA coating, comprising the following steps:

[0047] S1. Preparation of SIS membrane: Select the small intestine jejunum segment to prepare the SIS membrane, specifically: clean the small intestine jejunum segment and cut it into segments with a length of 8 to 12 cm, cut it longitudinally with a blade, completely peel off the mucosal layer, the outer muscle layer and the serosal layer, and prepare the SIS membrane by soaking it in a mixed solution of methanol and chloroform with a volume ratio of 1:1 for 10 hours, and rinse it with deionized water; then put it in EDTA containing trypsin and incubate it at 37°C for 10 hours, and rinse it with physiological saline, wherein the mass percentage content of trypsin is 0.05%, and the mass percentage content of EDTA is 0.05%; then stir it continuously in a mixed solution of 0.9% sodium dodecyl sulfate and 0.9% sodium chloride for 3 hours; finally, soak it in a mixed solution of 0.1% peracetic acid and 20% ethanol for 25 to 35 minutes, and rinse it with physiological saline;

[0048] S2. Mineralization treatment: After sealing the mucosal layer of the SIS membrane prepared in step S1, soak it in a mineralizing solution for 2 hours. After mineralization, wash and freeze-dry to obtain a hydroxyapatite-mineralized SIS-HA composite membrane, wherein the mineralizing solution is: 4% sodium chloride, 0.03% potassium chloride, 0.2% calcium chloride, 0.08% magnesium chloride hexahydrate, 0.1% disodium hydrogen phosphate, and 0.08% sodium bicarbonate.

[0049] Example 4: A method for preparing a SIS membrane based on a HA coating, comprising the following steps:

[0050] S1. Preparation of SIS membrane: Select the small intestine jejunum segment to prepare the SIS membrane, specifically: clean the small intestine jejunum segment and cut it into segments with a length of 8 to 12 cm, cut it longitudinally with a blade, completely peel off the mucosal layer, the outer muscle layer and the serosal layer, and prepare the SIS membrane by soaking it in a mixed solution of methanol and chloroform with a volume ratio of 1:1 for 15 hours, and rinse it with deionized water; then put it in EDTA containing trypsin and incubate it at 37°C for 15 hours, and rinse it with normal saline, wherein the mass percentage content of trypsin is 0.05%, and the mass percentage content of EDTA is 0.05%; then stir it continuously in a mixed solution of 0.9% sodium dodecyl sulfate and 0.9% sodium chloride for 5 hours; finally, soak it in a mixed solution of 0.1% peracetic acid and 20% ethanol for 35 minutes, and rinse it with normal saline;

[0051] S2. Mineralization treatment: After sealing the mucosal layer of the SIS membrane prepared in step S1, soak it in a mineralizing solution for 2.5 hours. After mineralization, wash and freeze-dry to obtain a hydroxyapatite-mineralized SIS-HA composite membrane, wherein the mineralizing solution is: 5% sodium chloride, 0.04% potassium chloride, 0.3% calcium chloride, 0.1% magnesium chloride hexahydrate, 0.12% disodium hydrogen phosphate, and 0.1% sodium bicarbonate.

[0052] Example 5: A method for preparing a SIS membrane based on a HA coating, comprising the following steps:

[0053] S1. Preparation of SIS membrane: Select the small intestine jejunum segment to prepare the SIS membrane, specifically: clean the small intestine jejunum segment and cut it into segments with a length of 8 to 12 cm, cut it longitudinally with a blade, completely peel off the mucosal layer, the outer muscle layer and the serosal layer, and soak the remaining submucosal layer and mucosal basal layer in 10mM EDTA with pH = 12 for 14 hours; then soak it in 1M NaCl solution with pH = 1 for 6 hours, soak it in 1M NaCl PBS solution for 14 hours, soak it in 10mM PBS solution with pH = 7.4 for 1.5 hours, and finally rinse it with sterile water;

[0054] S2. Mineralization treatment: After sealing the mucosal layer of the SIS membrane prepared in step S1, soak it in a mineralizing solution for 2.5 hours. After mineralization, wash and freeze-dry to obtain a hydroxyapatite-mineralized SIS-HA composite membrane, wherein the mineralizing solution is: 7% sodium chloride, 0.05% potassium chloride, 0.4% calcium chloride, 0.12% magnesium chloride hexahydrate, 0.15% disodium hydrogen phosphate, and 0.15% sodium bicarbonate.

[0055] Example 6: A method for preparing a SIS membrane based on a HA coating, comprising the following steps:

[0056] S1. Preparation of SIS membrane: Select the small intestine jejunum segment to prepare the SIS membrane, specifically: clean the small intestine jejunum segment and cut it into segments with a length of 8 to 12 cm, cut it longitudinally with a blade, completely peel off the mucosal layer, the outer muscle layer and the serosal layer, and soak the remaining submucosal layer and mucosal basal layer in 10mM EDTA with pH = 12 for 18 hours; then soak it in 1M NaCl solution with pH = 1 for 10 hours, soak it in 1M NaCl PBS solution for 18 hours, soak it in 10mM PBS solution with pH = 7.4 for 2.5 hours, and finally rinse it with sterile water;

[0057] S2. Mineralization treatment: After sealing the mucosal layer of the SIS membrane prepared in step S1, soak it in a mineralizing solution for 3 hours. After mineralization, wash and freeze-dry to obtain a hydroxyapatite-mineralized SIS-HA composite membrane, wherein the mineralizing solution is: 5% sodium chloride, 0.02% potassium chloride, 0.2% calcium chloride, 0.13% magnesium chloride hexahydrate, 0.15% disodium hydrogen phosphate, and 0.05% sodium bicarbonate.

[0058] The beneficial effects of the present invention are described below by experiments:

[0059] The experimental route of the present invention is as follows Figure 1 As shown, specifically

[0060] 1. Selection of small intestine segment

[0061] First, the fresh small intestine was divided into three sections: duodenum, jejunum, and ileum. Each section was then cut into 10 cm long segments. The sections were then cut longitudinally with a blade to completely peel off the mucosal layer, muscularis externa, and serosa. The remaining submucosal layer and mucosal basal layer were prepared as SIS raw materials. The target area of ​​the tissue was then selected using an Eclipse Ci-L polarized light camera microscope for 200x imaging. The tissue was allowed to fill the entire field of view as much as possible during imaging to ensure that the background light of each photo was consistent. Figure 2 After imaging, Image-Pro Plus 6.0 analysis software was used to measure the type I collagen pixel area in the three fields of view of each slice, denoted as A, and the corresponding type III collagen pixel area, denoted as B, and the type I and type III collagen pixel area ratio was calculated, denoted as C, and the results are shown in Table 1.

[0062] Table 1 Semi-quantitative analysis

[0063]

[0064] from Figure 2 As shown in Table 1, the content of type I collagen in the duodenum is the highest, and the content of type III collagen in the ileum is the highest. Type I collagen is related to tissue regeneration, and type III collagen is related to mechanical properties. In addition, the duodenum is limited in sampling, so the jejunum segment is the best choice as the raw material for inducing tissue regeneration.

[0065] 2. Preparation of SIS membrane

[0066] 2.1SIS-A

[0067] First, the fresh small intestine was placed at -80℃ for freeze drying for 24 hours, and rinsed with clean water for 5 minutes after thawing; then the small intestine was cut into 10 cm long segments, and then cut longitudinally with a blade, the mucosal layer, external muscle layer and serosal layer were completely peeled off, and the remaining submucosal layer and mucosal basal layer were prepared as SIS; then 0.1% peracetic acid (PAA) / 4% ethanol solution (100ml / 10g, the same below) was continuously stirred (300rpm) for 2 hours, and then washed with PBS for 15 minutes, and finally washed twice with deionized water, freeze-dried, sterilized with ethylene oxide, and set aside.

[0068] 2.2SIS-B

[0069] First, the fresh small intestine was cut into 10 cm long segments, and then cut longitudinally with a blade, and the mucosal layer, muscularis externa and serosa were completely peeled off, and the remaining submucosal layer and mucosal basal layer were prepared as SIS; then it was soaked in a mixed solution of methanol and chloroform (1:1, V / V) (100 ml / 1 g, the same below) for 12 hours, and rinsed with deionized water; then the SIS was incubated in 0.05% trypsin / 0.05% EDTA for 12 hours (37°C), and rinsed with saline; then it was continuously stirred (300 rpm) in 0.5% sodium dodecyl sulfate (SDS) 0.9% NaCl solution for 4 hours; finally, it was soaked in a mixed solution of 0.1% peracetic acid and 20% ethanol for 30 minutes, rinsed with saline, freeze-dried, sterilized with ethylene oxide, and set aside.

[0070] 2.3SIS-C

[0071] First, the fresh small intestine was cut into 10 cm long segments, and then cut longitudinally with a blade, the mucosal layer, the muscularis externa and the serosa were completely peeled off, and the remaining submucosal layer and mucosal basal layer were prepared as SIS; then the following chemical cleaning treatment was performed: first soaked in 100mM EDTA for 16h (NaOH adjusted pH = 12) (100ml / 1g, the same below); then soaked in 1M NaCl solution (1M HCl adjusted pH = 1) for 8h, then soaked in 1M NaCl PBS solution for 16h, then soaked in 10mM PBS solution (pH = 7.4) for 2h, and finally rinsed with sterile water (pH = 7.0) for 2h, freeze-dried, sterilized with ethylene oxide, and set aside.

[0072] The three prepared SIS were experimentally verified:

[0073] (1) Scanning electron microscopy (SEM) and cell nuclear staining experiments

[0074] The SIS membranes and SIS-N (small intestinal submucosa after mechanical treatment) prepared by the above three methods were subjected to SEM and cell nucleus staining. The experimental results are as follows Figure 3 As shown, from Figure 3It can be seen that: SEM results show that each group has nano-collagen fiber microstructures, the collagen fibers in the SIS-N group are intact and orderly arranged; the collagen fibers in the SIS-B and SIS-C groups are relatively intact, some fibers are broken, and the collagen fibers in the SIS-A group are obviously broken. The DAPI staining results show that residual cell nuclei can be seen in SIS-A, while no residual cell nuclei are seen in SIS-B and SIS-C. In summary, SIS-B and SIS-C can retain the original collagen fiber structure of SIS to the greatest extent while completely decellularizing.

[0075] (2) Residual DNA detection

[0076] After each group of tissues were crushed using a grinder, 100 mg of powder was taken into an EP tube, 300 μl of buffer GA was added, oscillated for 15 seconds, and placed at room temperature for 5 minutes. 30 μl of proteinase K solution was added, mixed, and treated at 56°C for 1-3 hours. 300 μl of buffer GB was added, fully inverted and mixed, placed at 70°C for 10 minutes, and briefly centrifuged to remove water droplets on the inner wall of the tube cap. 300 μl of anhydrous ethanol was added, fully oscillated and mixed for 15 seconds, and briefly centrifuged to remove water droplets on the inner wall of the tube cap. The solution and flocculent precipitate obtained in the previous step were added to an adsorption column CB3 (the adsorption column was placed in a collection tube), centrifuged at 12000g for 30 seconds, the waste liquid was discarded, and the adsorption column CB3 was placed back in the collection tube. 500 μl of buffer GD (with anhydrous ethanol added) was added to the adsorption column CB3, centrifuged at 12000g for 30 seconds, the waste liquid was discarded, and the adsorption column CB3 was placed back in the collection tube. The adsorption column CB3 was placed back in the collection tube. Add 500μl of rinse solution PW to the adsorption column CB3, centrifuge at 12000g for 30s, and discard the waste liquid. Put the adsorption column CB3 back into the collection tube, centrifuge at 12000g for 2min, discard the waste liquid, and leave it at room temperature for 10min to completely dry the residual rinse solution in the adsorption material. Transfer the adsorption column CB3 to a clean centrifuge tube, add 100μl of TE elution buffer to the middle part of the adsorption membrane in mid-air, leave it at room temperature for 5min, centrifuge at 12000g for 2min, and collect the solution in a centrifuge tube. Add the solution obtained by centrifugation to the adsorption column CB3 again, leave it at room temperature for 2min, centrifuge at 12000g for 2min, and collect the solution in a centrifuge tube.

[0077] The residual DNA content of SIS prepared by the three methods was detected, and the results were as follows: Figure 4 As shown, from Figure 4It can be seen that the residual DNA content detection results showed that SIS-N had the highest residual DNA content, which was 935.13±99.30ng / mg, while SIS-B and SIS-C had the lowest residual DNA contents, among which the residual DNA content of SIS-B was 35.37±5.92ng / mg, and the residual DNA content of SIS-C was 43.90±7.78ng / mg. The difference was statistically significant (P<0.05), which was consistent with the DAPI staining results.

[0078] (3) ELISA experiment

[0079] ELISA was performed on the remaining active factors contained in SIS (SIS-A, SIS-B and SIS-C) and SIS-N prepared by three methods to compare the degree of destruction of the original active factors of SIS by these three preparation methods, so as to select the best preparation method.

[0080] A. Coating: Use 0.05M pH=9 carbonate coating buffer to dilute glycosaminoglycan (GAG), transforming growth factor-β (TGF-β), vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) antibodies to a protein content of 1-10 μg / ml. Add 0.1 ml to each reaction well of the polystyrene plate and incubate at 4°C overnight; the next day, discard the solution in the well and wash 3 times with washing buffer, 3 minutes each time.

[0081] B. Sample addition: Accurately weigh the tissue mass of each group of samples, add PBS at a mass-volume ratio of 1:9, use a homogenizer to homogenize the tissue, centrifuge the homogenate at 5000×g for 10 minutes, and take the supernatant for testing. Add 0.1ml of the sample to be tested at a certain dilution to the above-mentioned coated reaction wells, incubate at 37℃ for 1 hour, and then wash. (At the same time, make blank wells, negative control wells and positive control wells).

[0082] C. Add enzyme-labeled antibody: Add 0.1 ml of freshly diluted enzyme-labeled antibody (dilution after titration) to each reaction well, incubate at 37°C for 0.5-1 h, and wash.

[0083] D. Add substrate solution for color development: Add 0.1 ml of TMB substrate solution prepared temporarily to each reaction well and incubate at 37°C for 10-30 min. Stop reaction: Add 0.05 ml of 2M sulfuric acid to each reaction well.

[0084] E. Finally, measure the OD value: On the ELISA detector, at 450nm (410nm if ABTS is used for color development), adjust the blank control well to zero and measure the OD value of each well. If it is greater than 2.1 times the specified negative control OD value, it is positive.

[0085] The experimental results are as follows Figure 5As shown: ELISA results show that the content of biologically active factors (GAG, TGF-β, VEGF and bFGF) in SIS-A, SIS-B and SIS-C are significantly lower than that in SIS-N, among which SIS-B has a smaller decrease, which is reduced to about 65% of SIS-N.

[0086] In summary, SIS-B was selected as the experimental material to further prepare the SIS-HA composite membrane.

[0087] 3. Preparation of SIS-HA composite membrane

[0088] Take 200mL of deionized water in a 250mL glass beaker, add 14.6g NaCl, 0.09g KCl, 0.70g CaCl2, 0.25g MgCl2·6H2O, 0.30g Na2HPO4 and 0.21g NaHCO3 powder in turn, stir until completely dissolved, and adjust the volume to 250mL. Then seal the mucous membrane layer of the SIS membrane with plastic paper, and then immerse it in 100mL of freshly prepared mineralization solution. After immersion for 2h at room temperature and pressure, take out the mineralized SIS membrane, wash it thoroughly 3 times, and freeze-dry it to obtain the SIS-HA composite membrane.

[0089] 3.1 Quantitative analysis of calcium using SEM-EDS analysis

[0090] The SIS and the prepared SIS-HA composite membrane were subjected to quantitative analysis of calcium using SEM-EDS analysis. The experimental results are shown in Figure 6 and Figure 7 As shown, the EDS analysis results showed that the calcium content of SIS-HA was 6.1%.

[0091] Table 2 EDS analysis

[0092]

[0093] 3.2 Hydrophilicity test

[0094] The dried SIS and SIS-HA composite films (1 cm × 1 cm) were placed in the detection area of ​​the contact angle meter. Deionized water was dropped on the membrane surface for 15 seconds and then the image was read to detect the wettability. Three samples were taken for each collagen membrane to calculate the average and standard deviation.

[0095] The experimental results are as follows Figure 8 As shown, the hydrophilicity analysis results showed that the water contact angles of SIS and SIS-HA were 63.21±3.25° and 64.70±3.42°, respectively, with no statistical difference, indicating that the HA coating had no significant effect on the hydrophilicity of the SIS surface.

[0096] 3.3 Mechanical properties experiment

[0097] The SIS and SIS-HA composite films were cut into 2.5×2.5 cm sizes, dried at 60°C and -0.085 MPa for 2 h, and fixed on both sides with a universal testing machine for tensile testing to determine the tensile strength and elongation at break; the films were measured three times respectively, and the average and standard deviation were calculated.

[0098] The experimental results are as follows Fig. 9 As shown, the tensile strength analysis results showed that there was no significant difference in tensile strength and elongation between SIS and SIS-HA, indicating that the HA coating did not destroy the original collagen fiber mechanical structure of SIS.

[0099] 3.4 In vitro degradation rate experiment

[0100] The dried SIS and SIS-HA composite membranes (1cm×1cm), 15 samples in each group, were freeze-dried and weighed, recorded as m0. Then, the two groups of samples were placed in 5mL type I collagenase solution (5mg / mL) and placed in a 37℃ water bath. Three samples were taken out at 1d, 3d, 7d, and 14d, rinsed with deionized water, freeze-dried, and weighed, recorded as m1. The degradation rate q was calculated according to the formula: Calculate the mean and standard deviation of the degradation rate at different times. The dried SIS and SIS-HA composite membranes (1cm×1cm), 15 samples in each group, were freeze-dried and weighed separately, recorded as m0. Then, the two groups of samples were placed in 5mL PBS and placed in a 37℃ water bath. Three samples were taken out at 2, 4, 6, 10 and 16 weeks, rinsed with deionized water, freeze-dried, and weighed separately, recorded as m1. The degradation rate q was calculated according to the formula: Calculate the mean and standard deviation of the degradation rate at different times.

[0101] The results are as follows Fig.10 As shown, the in vitro degradation rate results showed that the in vitro degradation rate of SIS-HA was significantly lower than that of SIS, which may be due to the fact that the HA coating protected SIS from degradation by PBS and collagenase.

[0102] 3.5 Cellular Immunomodulatory Ability

[0103] Macrophage polarization was detected using Raw264.7 cells cultured with SIS. 5Cells per well were seeded on different cell membranes and cultured in Dulbecco's modified Eagle's medium (37°C, 5% CO2) containing 10% fetal bovine serum (FBS) and 1% antibiotics (penicillin-streptomycin, SigmaAldrich) for 1 day in vitro to observe the expression of M1 / M2 polarization markers. M2 markers were Arg-1 and CD206, and the number of CD206-positive cells was detected by immunofluorescence staining (1:150). DAPI was used for nuclear staining according to the manufacturer's protocol, and the staining of the specimens was observed using a confocal laser scanning microscope.

[0104] The experimental results are as follows Fig.11 As shown, the expression of Arg-1 and CD206 in the SIS group was significantly upregulated compared with the control group, indicating that SIS has the effect of inducing macrophages to polarize into regenerative M2 cells, thereby promoting tissue regeneration.

[0105] 3.6 Human periodontal ligament cells (PDLSCs) adhesion experiment

[0106] The SIS and SIS-HA composite membranes were trimmed into a circle with a diameter of 15 mm, sterilized with 75% ethanol for 1 h, then irradiated with ultraviolet light for 3 h, washed with PBS, and soaked in α-MEM overnight. 4 The cells were inoculated onto the membrane at a density of 100 / well. After culturing for 24 hours, they were fixed with 4% paraformaldehyde for 10 minutes and then permeabilized with 0.5% Triton X-100 for 10 minutes. After blocking the cells with 1% bovine serum albumin, they were incubated with fluorescein phosphatidylcholine overnight at 4°C, and the cell nuclei were stained with protein. The cell morphology and the adhesion of cells to the fibers were observed under a laser confocal microscope (CLSM). In addition, the adhesion of cells to each group of membranes was observed under SEM. They were fixed with 2.5% glutaraldehyde for 30 minutes, and then dehydrated with graded ethanol solutions of 30%, 50%, 70%, 80%, 90%, 95% and 100% for 15 minutes. Subsequently, the samples were freeze-dried and observed under SEM.

[0107] The experimental results are as follows Fig.12 As shown in the figure, DAPI is a stain for the nucleus, Actin is a stain for the cytoskeleton, Merge is a double stain for the nucleus and cytoskeleton, and the SEM and CLSM results show that after 24 hours, the PDLSCs cells are stably attached to the SIS and SIS-HA membranes and completely extend their pseudopodia, indicating that the HA coating has no adverse effect on cell adhesion.

[0108] 3.7PDLSCs proliferation assay

[0109] CCK8 assay was used to assess cell viability according to the manufacturer's protocol. The extracts of different membranes were soaked in α-MEM with 10% bovine serum albumin in a thermostatic oscillator (37°C, 100 rpm). PDLSCs were treated with the extracts of SIS and SIS-HA membranes for 1, 3, 5, and 7 days, respectively, and then the culture medium in each well was replaced with α-MEM culture medium containing 10% CCK-8 reagent. Incubation was continued for 2 h in the dark at 37°C. The absorbance at a wavelength of 450 nm was measured using a microplate reader. Live / dead analysis was performed after 1, 3, 5, and 7 days of culture. The Live / Dead Cell Imaging Kit was used for this experiment according to the kit protocol. After 1, 3, 5, and 7 days of culture, PDLSCs were fixed with 4% paraformaldehyde for 10 min, then washed with PBS, and live / dead staining solution was added to the specimens. The samples treated with the live / dead reagent were incubated at 37°C and 5% carbon dioxide for 30 min. Finally, the samples were rinsed with PBS again and imaged using CLSM. Calcein interacts with live cells in green, and ethidium homodimer-1 interacts with dead cells in red.

[0110] The experimental results are as follows Fig.13 As shown, the results of CCK-8 and live-dead staining showed that after SIS and SIS-HA were cultured with PDLSCs for 1, 3, 5, and 7 days, respectively, PDLSCs in each group showed a higher survival rate, and there was no statistically significant difference among the groups, indicating that the HA coating had no adverse effect on cell proliferation.

[0111] 3.8 Human periodontal ligament cell migration ability experiment

[0112] Transwell and scratch healing assays were used to detect the migration of PDLSCs. 5 Add 200ul of cells to an incubator containing 0% FBS, and add 1ml of 0% FBS culture medium to a 24-well plate. After culturing in an incubator at 37°C for 48h, remove the chamber and then soak it in 95% ethanol for 20min. Wash with PBS and stain with 2% crystal violet for 30min. Finally, photograph the cells under a microscope. In the scratch healing experiment, PDLSCs were planted in a 6-well culture plate and scratched with a 200-microliter pipette tip. When the density reached about 90%, a "scratch" was produced. Wash with PBS until there are no suspended cells. Immediately after the scratch (0h), take a phase contrast microscope, culture PDLSCs with 0% FBS culture medium, and take pictures under a microscope every 12h until the scratch heals.

[0113] The experimental results are as follows Fig.14 As shown in the figure, the scratch and Transwell experiment results showed that both SIS and SIS-HA could promote the migration of PDLSCs cells, and the number of migrated cells of SIS-HA was the largest, and the difference was statistically significant, indicating that HA coating could significantly promote cell migration.

[0114] 3.9 Osteogenic differentiation ability of PDLSCs

[0115] 5×10 4 PDLSCs were seeded on blank control group, SIS and SIS-HA composite membranes, respectively, and cultured in osteogenic induction medium containing 5% fetal bovine serum, 8 mol / L dexamethasone, 50 mg / L ascorbic acid and 10 mol / L α-glycerophosphate for 7 days and 14 days, respectively. After 7 days of co-culture, the cells were fixed with 4% paraformaldehyde for 10 minutes and washed with deionized water. After staining with alkaline phosphatase detection kit (ALP) at room temperature for 1 hour, they were washed with deionized water. The stained mineral deposits can be observed under the microscope. After 14 days of co-culture, the cells were fixed with 4% paraformaldehyde for 10 minutes and washed with deionized water. Then, they were stained with Alizarin Red Detection Kit (ARS) solution (pH 4.1) at room temperature for 20 minutes and washed with deionized water. The stained mineral deposits can be observed under the microscope.

[0116] The experimental results are as follows Fig.15 As shown, the ALP and ARS staining results showed that the SIS-HA group had the deepest staining, with obvious mineralized nodules, indicating that the HA coating can significantly promote the osteogenic differentiation of PDLSCs cells.

[0117] 3.10 3D reconstruction and bone healing experiment in rats with periodontal bone defects

[0118] Wistar rats (male, 8 weeks old, SPF, Chengdu, China) (n=5) were used for the experiment. The surgery was performed under sodium pentobarbital anesthesia (40 mg / kg body weight). A mandibular cheek bone defect (3×2×1.5 mm) was created with a slow-speed dental drill. 3 ). The critical bone defect was located approximately 1 mm distal to the anterior edge of the mandible, while the coronal edge of the bone defect was located 1 mm from the apex of the alveolar bone. The rats were randomly divided into 3 groups: (1) blank control group, (2) SIS group, and (3) SIS-HA group. At 4 and 6 weeks after surgery, the rats were killed under an overdose of sodium pentobarbital anesthesia, and the mandibular tissues were removed and fixed with 4% paraformaldehyde. CT, VOX, and CT analysis software were used to reconstruct the images and perform 3D reconstruction analysis.

[0119] The experimental results are as follows Fig.16 As shown, 4 and 6 weeks after surgery, the bone defect healing area in the SIS and SIS-HA groups was significantly increased compared with the control group, among which the SIS-HA group had the best osteogenesis effect, indicating that HA coating can significantly promote osteogenesis.

[0120] 3.11 Histochemical staining of periodontal bone defects in rats

[0121] 15. Mandibular tissue was decalcified with 10% EDTA at 4°C for 1 month and then dehydrated in ethanol solution. After being treated with xylene, the specimens were embedded in paraffin and the cross-sections of the osteochondral defect area were cut (thickness 5 μm). Hematoxylin-eosin (H&E) and trichrome (Masson) staining were used to evaluate periodontal tissue regeneration in accordance with the manufacturer's protocol. BMP-2 immunofluorescence single staining was used to detect BMP-2 positive cells, and DAPI was used to stain the cell nucleus to observe the osteogenesis effect. The staining of the specimens was observed using CLSM.

[0122] The experimental results are as follows Fig.17 As shown, the results of histochemical staining showed that 4 and 6 weeks after surgery, the bone defect healing area of ​​the SIS and SIS-HA groups was significantly increased compared with the control group, among which the SIS-HA group had the best osteogenesis effect, indicating that HA coating can significantly promote osteogenesis.

[0123] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which are all covered by the protection scope of the present invention.

Claims

1. A method for preparing a SIS membrane based on a hydroxyapatite coating, characterized in that: It includes the following steps: S1. Preparation of SIS membrane: The submucosal layer and mucosal basal layer of the small intestine jejunum segment were selected to prepare the SIS membrane; The small intestine jejunum segment was cleaned and cut into segments of 8 to 12 cm in length. The segments were cut longitudinally with a blade, and the mucosal layer, muscularis externa and serosa were completely peeled off. The remaining submucosal layer and mucosal basal layer were used to prepare the SIS membrane. The specific operation of preparing the SIS membrane is as follows: The submucosal layer and the mucosal basal layer were immersed in a mixed solution of methanol and chloroform in a volume ratio of 1:1 for 12 hours, and then rinsed with deionized water; then incubated in EDTA containing trypsin at 37°C for 12 hours, and then rinsed with saline, wherein the mass percentage content of trypsin was 0.05%, and the mass percentage content of EDTA was 0.05%; then stirred continuously for 4 hours in a mixed solution of 0.5% sodium dodecyl sulfate and 0.9% sodium chloride; finally, immersed in a mixed solution of 0.1% peracetic acid and 20% ethanol for 30 minutes, and then rinsed with saline; S2. Mineralization treatment: After sealing the mucosal layer of the SIS membrane prepared in step S1, soak it in a mineralizing solution for 1.5 to 3 hours. After mineralization, wash and freeze-dry to obtain a hydroxyapatite-mineralized SIS-HA composite membrane, wherein the mineralizing solution is a mixed solution of sodium chloride, potassium chloride, calcium chloride, magnesium chloride hexahydrate, disodium hydrogen phosphate and sodium bicarbonate, and the mass percentage concentration of each raw material in the mineralizing solution is: 3 to 8% sodium chloride, 0.02 to 0.05% potassium chloride, 0.1 to 0.5% calcium chloride, 0.05 to 0.15% magnesium chloride hexahydrate, 0.08 to 0.2% disodium hydrogen phosphate, and 0.05 to 0.15% sodium bicarbonate.

2. The method for preparing a SIS membrane based on a hydroxyapatite coating according to claim 1, characterized in that: In the step S1, the SIS membrane is prepared using the jejunum segment of the small intestine of pigs.

3. The method for preparing a SIS membrane based on a hydroxyapatite coating according to claim 1, characterized in that: The mass percentage concentration of each raw material in the mineralization solution in step S2 is: 5.84% sodium chloride, 0.036% potassium chloride, 0.28% calcium chloride, 0.1% magnesium chloride hexahydrate, 0.12% disodium hydrogen phosphate, 0.084% sodium bicarbonate.

4. A SIS membrane based on hydroxyapatite coating prepared according to the method of any one of claims 1 to 3.